New economies and innovation for developing countries: The case of Intel in Costa Rica - Vargas Alfaro, Leiner (2002)
The paper presents the specialisation patterns and indexes of the Central American economies based on the CAN database of CEPAL and reports on recent research on these issues and compare this “Intel Island” observation with the “Mobil Valley” case of growth of the electronics sector in the relative less developed region of North Jutland, Denmark. Here the knowledge base, research and education was established prior to investments (with EU subsidies) in assembly factories together with growth in investment in private R&D departments, joint industry-university collaboration, a science park etc., which all in all gives an almost opposite picture of a sustainable development of the new economy. On this basis, the paper evaluates and discuss how to promote dynamic effects of the new economy in the context of re-exportation-based FDI in developing countries. The industrialisation picture of the trade statistics of the rest of Central America resembles very much the Costa Rican one in recent years in terms of growth in manufacturing exports. The paper also opens a discussion of their conditions for participation in the new economy viz-a-viz the prevailing re-exportaion regimes of the countries. Some general lessons and principles for the new economy as a strategy for development are offered as a conclusion.